Microencapsulation and flavor stability of spray-dried oleoresin from water dropwort (Oenanthe javanica) and kacip fatimah (Labisia pumila) - Pattiram, Parveen Devi (2013)
Water Dropwort (Oenanthe javanica) is a perennial herb with distinctive aroma and taste. It is cultivated in marshy places of Asia and Australia. Besides that, “Kacip Fatimah” (Labisia pumila) is a small herbaceous under shrub that roots and stems. There were three objectives established in this study that are identification and sensory characterization of compounds from water dropwort (Oenanthe javanica) and “Kacip Fatimah” (Labisia pumila). Second objective is stability of aroma-active constituents in oleoresin of Water dropwort (Oenanthe javanica) and “Kacip Fatimah” (Labisia pumila) herbs during spray drying at 170±2oC and 180±2oC. Thirdly is to study the effect of storage condition on the release flavors profiles of the encapsulated water dropwort (Oenanthe javanica) and “Kacip Fatimah” (Labisia pumila) oleoresin. The first part in this study was established by GC-MS and GC-O analysis to identify the chemical constituents of the oleoresins from both water dropwort and “Kacip Fatimah” leaves. A total of 41 compounds were identified in Water dropwort. The major compound obtained was richer in diterpenes such as incensole (9.04%). However, 33 compounds were obtained from “Kacip Fatimah” and predominated with sesquiterpenes alcohol such as T-cadinol (13.33%). Furthermore, stability of aroma-active constituents in oleoresin of Water dropwort and “Kacip Fatimah” were successfully conducted by using microencapsulation technique with a combination of gum Arabic (1.5%) and food grade gelatin (2.5%) in the formulation of spray dried encapsulated leaves extracts whereby,inlet temperatures of 170±2 oC and 180±2 oC with constant outlet temperature 84oC±4 oC and the feed rate of 6 rpm were established for both leaves. At drying temperature 170±2 oC and 180±2 oC, a total of volatile compounds of water dropwort were reduced from 41 compounds to 9 and 6 compounds respectively. Incensole has the highest concentration at these both drying temperatures (29.49% and 37.49%) respectively. Meanwhile, in “Kacip Fatimah” also found reduction in number of volatile compounds from initially 33 compounds to 25 and 12 compounds respectively. T-cadinol has among the highest concentration at these drying temperatures 170±2 oC (22.56%) and 180±2 oC (33.18%). Finally, study the effect of storage condition on the release flavors profiles of the encapsulated water dropwort (Oenanthe javanica) and “Kacip Fatimah” (Labisia pumila) oleoresin was established. The microcapsules were stored under the same temperature at 45±2 oC and 24 % RH for further studies. The microcapsules were maintained for 30 days in a climate chamber. The numbers of volatile compounds in microcapsules of water dropwort were reduced drastically after day 24. For instance, at drying temperature 170±2 oC, encapsulated water dropwort has reduced to 2 compounds as compared with day 6 (6 compounds). Encapsulated “Kacip Fatimah” also showed the same reduction whereby, a total of 5 compounds were detected at 24 days of storage as compared to 25 compounds detected at 6 days storage. At 180±2 oC drying temperature,encapsulated water dropwort and “Kacip Fatimah” showed the volatile compounds reduced after 18 days of storage. A total of 4 and 3 compounds respectively were detected as compare with 6 days of storage (5 and 2 compounds were identified) respectively. Volatile compounds were no detected in both encapsulated water dropwort and “Kacip Fatimah” at day 30 which is probably caused by the invisible cracks on the surface of the microcapsules. Overall, particle size and emulsion size of microcapsules also increased due to agglomeration occurs after storage. From this study, it can be concluded that encapsulated water dropwort and “Kacip Fatimah”, incensole and Tcadinol have the highest concentration during storage.